Type I interferon response-related microglial Mef2c deregulation at the onset of Alzheimer's pathology in 5×FAD mice - Feng Xue; Jing Tian; Chunxiao Yu; Heng Du; Lan Guo (Neurobiology of Disease, 2021)
Alzheimer's disease (AD) is a chronic neurodegenerative disorder with multifactorial etiology. The role of microglia in the pathogenesis of AD has been increasingly recognized in recent years; however, the detailed mechanisms shaping microglial phenotypes in AD-relevant pathological settings remain largely unresolved. Myocyte-specific enhancer factor 2C (Mef2C) is a transcription factor with versatile functions. Recent studies have attributed aging-related microglial changes to type I interferon (IFN-I)-associated Mef2C deregulation. In view of the close relationship between brain aging and AD, it is of great interest to determine microglial Mef2C changes in AD-related conditions. In this study, we have found that suppressed Mef2C nuclear translocation was an early and prominent microglial phenotype in a mouse model of brain amyloidosis (5×FAD mice), which exacerbated with age. Echoing the early Mef2C deregulation and its association with microglial activation, transcriptional data showed elicited IFN-I response in microglia from young 5×FAD mice. Amyloid beta 42 (Aβ42) in its oligomeric forms promoted Mef2C deregulation in microglia on acute organotypic brain slices with augmented microglial activation and synapse elimination via microglial phagocytosis. Importantly, these oligomeric Aβ42-mediated microglial changes were substantially attenuated by blocking IFN-I signaling. The simplest interpretation of the results is that Mef2C, concurring with activated IFN-I signaling, constitutes early microglial changes in AD-related conditions. In addition to the potential contribution of Mef2C deregulation to the development of microglial phenotypes in AD, Mef2C suppression in microglia may serve as a potential mechanistic pathway linking brain aging and AD.